The Influence of Shopee Pay Later Usage on the Consumptive Behavior of FKIP Students at Universitas Muhammadiyah Bengkulu - Lestari, Nurdiah Ririn; Suharmi , Suharmi; Suryani, Ade Irma (Utami Publisher, 2025)
The purpose of this study is to determine the influence of Shopee PayLater usage on students' consumptive behavior. Shopee PayLater is a payment method in the form of an instant loan that allows users to receive goods first and make payments later, either in the following month or through installments. This study employs a quantitative approach to examine how Shopee PayLater usage affects students' consumptive behavior. Data were collected through questionnaires distributed to 37 student respondents. The results of the hypothesis testing showed a significance value (sig) of 0.001. This indicates a significant relationship, as the significance value is less than 0.05. Therefore, it can be concluded that the alternative hypothesis (Ha), which states that Shopee PayLater usage has a positive effect on students' consumptive behavior, is accepted. Conversely, the null hypothesis (Ho) is rejected, indicating that Shopee PayLater usage (X) indeed influences students' consumptive behavior (Y).